Factors influencing implementation and sustainability of interventions to improve oral health and related health behaviours in adults experiencing severe and multiple disadvantage: a mixed-methods systematic review - John, Deepti A.; Adams, Emma A.; McGowan, Laura J.; Joyes, Emma C.; Richmond, Catherine; Beyer, Fiona R.; Landes, David; Watt, Richard G.; Sniehotta, Falko F.; Paisi, Martha; Bambra, Clare; Craig, Dawn; et al. (BMJ open, 2024)
OBJECTIVES: Among people experiencing severe and multiple disadvantage (SMD), poor oral health is common and linked to smoking, substance use and high sugar intake. Studies have explored interventions addressing oral health and related behaviours; however, factors related to the implementation of these interventions remain unclear. This mixed-methods systematic review aimed to synthesise evidence on the implementation and sustainability of interventions to improve oral health and related health behaviours among adults experiencing SMD. - METHODS: Bibliographic databases (MEDLINE, EMBASE, PsycINFO, CINAHL, EBSCO, Scopus) and grey literature were searched from inception to February 2023. Studies meeting the inclusion criteria were screened and extracted independently by two researchers. Quality appraisal was undertaken, and results were synthesised using narrative and thematic analyses. - RESULTS: Seventeen papers were included (published between 1995 and 2022). Studies were mostly of moderate quality and included views from SMD groups and service providers. From the qualitative synthesis, most findings were related to aspects such as trust, resources and motivation levels of SMD groups and service providers. None of the studies reported on diet and none included repeated offending (one of the aspects of SMD). From the quantitative synthesis, no difference was observed in programme attendance between the interventions and usual care, although there was some indication of sustained improvements in participation in the intervention group. - CONCLUSION: This review provides some evidence that trust, adequate resources and motivation levels are potentially important in implementing interventions to improve oral health and substance use among SMD groups. Further research is needed from high quality studies and focusing on diet in this population. - PROSPERO REGISTRATION NUMBER: CRD42020202416.